Allozyme analysis of the four species of Hypostomus (Teleostei: Loricariidae) from the Ivaí river, upper Paraná river basin, Brazil - doi: 10.4025/actascibiolsci.v35i4.16355 (Acta Scientiarum. Biological Sciences, 2013)
Allozyme electrophoresis analysis were performed in four species of Hypostomus (Loricariidae), H. albopunctatus, H. hermanni, H. regani, e Hypostomus sp. 1/NUP 5612 from the Ivaí river, a tributary of the upper Paraná river. The study of 14 loci revealed diagnostic characters and exclusive alleles in a low frequency. The heterozygosity ranged from 0.000 in H. albopunctatus to 0.199 in H. hermanni, which was higher than the heterozygosity in other samples of Hypostomus in literature, as well as in other fish groups. Hypostomus albopunctatus and H. regani revealed higher similarity (I = 0.804), while H. hermanni and Hypostomus sp. 1/NUP 5612 showed the least genetic identity (I = 0.569). All samples were genetically distinguished, despite there were several shared alleles. The FST value was 0.671, showing a high genetic differentiation among the samples. Hypostomus sp. 1/NUP 5612 was genetically distinguished from the three congeners by the loci Adh-A and G3pdh-B and by present rare exclusive alleles in other six enzymatic systems.